Cu2−xSe nanooctahedra: controllable synthesis and optoelectronic properties1. Issue 9 (7th March 2015) - Wang, Wenliang; Zhang, Li; Chen, Guihuan; Jiang, Jun; Ding, Tao; Zuo, Jian; Yang, Qing
<x xml:space="preserve">Abstract</x> A phosphine-free route to single crystalline copper selenide (Cu2−xSe) nanocrystals with a well-defined octahedral shape and good photodetector performance.